Citral Encapsulation for an Antimicrobial Natural Powdered-Additive: Performance of Wall Material and Drying Process - Matiacevich, S; Alarcon-Moyano, J (John Wiley and Sons Inc, 2024)
Citral encapsulation was analyzed by spray and freeze-drying to obtain an antimicrobial additive in powder. Different formulations containing alginate and modified starch (Capsul®) as encapsulating agents (1% and 3% w/w, respectively) and maltodextrin as a wall material at different concentrations (varied from 1:1–1:4 Citral:Maltodextrin) were prepared. The powders were evaluated for physical and antimicrobial properties against Escherichia coli to obtain a natural antimicrobial food additive. Citral:Capsul:Maltodextrin powders obtained by spray-drying showed the best physical properties, considering encapsulation yield (EY) (75%–80%), encapsulation efficiency (EE) (~78%), and particle size (5–10 μm), and a higher microbial inhibition at a lower additive concentration (1.5%–2% w/w), independently of maltodextrin concentration used. Powders obtained by freeze-drying emulsions showed an EY ~70%, EE ~70%, particle sizes between 80 and 1250 μm, and a higher percentage of rehydration for antimicrobial activity (2.5%–4% w/w). An increase in maltodextrin concentration led to a decrease in %EE, an increase in particle size, and the powder concentration required to inhibit microbial growth. Therefore, the formulation 1:1:1 Citral:Capsul:Maltodextrin showed by spray-drying showed the best characteristics to obtain a natural antimicrobial additive. © 2023 AOCS.